Development of Alternative and Augmentative Communication Media System for Autism Spectrum Disorder with Complex Communication Needs - Rezkiani, Kiki; Aprilia, Imas Diana (Journal of Education for Sustainability and Diversity, 2023)
This study aims to help children with autism spectrum disorder (ASD) with difficulties communicating, especially expressive language. This research develops alternative and augmentative communication media needed in expressing his wishes to the people around him in everyday life. This study uses a research and development (R&D) model with a qualitative descriptive approach to explaining alternative and augmentative communication media use. This research results in an alternative and augmentative communication media called "Famopa". The development of the media has been adapted to the subject's knowledge in shape recognition, symbol systems, and the subject's communication skills and effectively helps the subject express his wishes. From the development of alternative and augmentative communication media, "Famopa", the expected implication is that it can help subjects communicate with their surroundings, especially in expressing their desires.